Potassium leaching and nutrient content in soil and alfalfa’s response to a dose of vinasse - Flores Rodríguez Patricia; Gavi Reyes, Francisco; Torres Benites, Elibeth; Hernández Acosta Elizabeth (Revista Mexicana de Ciencias Agrícolas, 2018)
Under greenhouse conditions and based on the concentration of potassium (K+) in the chemical characterization of Vinasse, the effect of different doses (0. 250 y 500 kg ha-1 de K+) was evaluated in the soil, in columns of polyvinyl chloride (PVC), using suction lysimeters at two depths (23 and 46 cm) and samples at the end of the column (75 cm). In Leaching, the K concentration, the effect on pH and the electric conductivity (CE) was evaluated; as the crop indicator, alfalfa was used (Medicago sativa), making 2 cuts in a period of 120 days and applying vinasse at the beginning of the experiment and then again after the first cut. In plant samples, the variables were dry material, NT, B, Ca, Cu, Fe, K, Mg, Mn, Na, P, Zn and NO3 in soil, CE, pH, NH4, NO3, P, K, Na, Ca, Mg, Fe, Cu, Zn Mn abd MO (organic material) was considered. In the statistical analysis of the K dose of 500 kg ha-1 there was an effect on the soil fertility, registering an increase in MO, NH4, P, Ca, Na, Mg, Fe, Cu, Zn, Mn y K. La CE and K. The greatest effect (p< 0.05), was in 10cm of soil. In leached soil, the effect (p< 0.05) was at a depth of 23 cm for both applications of vinasse. The pH did not show changes (p< 0.05), with the application of vinasse. In plant tissue, the nutrients that increased (p< 0.05) were for P= 1939.2 and Zn= 28.63 mg kg-1 for the dose of 500 kg ha-1, with respect to the control, P= 1025.2 and Zn= 14.17 mg kg-1 respectively. For the former, the use of Vinasse as an in input of plant nutrition is recommended.